2015
DOI: 10.1037/pha0000031
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in self-report and behavioral measures of disinhibition predicting marijuana use across adolescence.

Abstract: Disinhibition has been consistently linked to substance use across development. Recent research suggests, however, that these relations may be influenced by both sex and measurement approach. The current study examined the moderating effect of sex on the association between behavioral and self-report measures of disinhibition and marijuana use across adolescence. Participants were 115 boys and 89 girls initially evaluated at grade 8 using a laboratory behavioral assessment and self-report questionnaires of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 66 publications
1
13
1
Order By: Relevance
“…We noted a similar finding for the relationship between cannabis use and NSSI. Such shared genetic pathways may include a general liability to impulsive or disinhibited behaviors, which are related to both cannabis use (Felton et al, 2015) and NSSI (Glenn & Klonsky, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We noted a similar finding for the relationship between cannabis use and NSSI. Such shared genetic pathways may include a general liability to impulsive or disinhibited behaviors, which are related to both cannabis use (Felton et al, 2015) and NSSI (Glenn & Klonsky, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Sensation seeking is the most widely studied impulsivity-related trait for marijuana use and there is consistent evidence that sensation seeking is a robust predictor of marijuana use in both adults (e.g., Alston, 1994;Trocki et al, 2009;Quinn and Harden, 2013) and adolescents (e.g., Andrucci et al, 1989;Arnett and BalleJensen, 1993;Castellanos-Ryan et al, 2013;Felton et al, 2015).…”
Section: Separable Impulsivity Traits: the Upps-p Modelmentioning
confidence: 99%
“…Adolescents high in sensation seeking are more likely to use marijuana (e.g., Martin et al, 2002;Stanton et al, 2001) and use marijuana more frequently (e.g., Donohew et al, 1999;Felton et al, 2015). Additionally, adolescent sensation seekers are more likely to experience negative marijuana consequences, including trouble at school and at home (e.g., Hendershot et al, 2011;, and be diagnosed with marijuana dependence (e.g., Ames et al, 2005).…”
Section: Separable Impulsivity Traits: the Upps-p Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an important consideration given that traditional neuropsychological measures may not capture every-day dysfunction in substance using populations [43]. In a longitudinal study by Felton and colleagues [44], self-reported and behavioral measures of disinhibition in 8 th grade prospectively predicted increased marijuana use across high school students, regardless of gender. Self-reported apathy and executive dysfunction on the Frontal Systems Behavioral Scale (FrSBe) have also been related to severity of marijuana use [45].…”
Section: Introductionmentioning
confidence: 99%